Qualidade de vida de estudantes do ensino fundamental da escola Maria Peregrina, sob influência da pedagogia de projetos - Wada, Max Lopes (2016)
Introduction: Quality of life (QL) is a current term used by the post-modern humanity, which is related to the culture of health and life style. In this regarding, this study analyzed aspects of QL in a school environment. Thus, the current revelations of the World Health Organization on the health concept reflect the well-being of the individual as a parameter to be healthy. In the same direction, the recent concepts of QL also decline to dimensions involving emotional, cultural, psychological and spiritual components. It highlights within these components the school environment and the family of the students that integrate all reality of society, since the evaluation of QL has meaningful social relevance. Purpose: To evaluate the QL of students participating in an alternative educational system, at the elementary school level in the city of São José do Rio Preto, Sao Paulo, Brazil. This differentiated educational system is based on the pedagogy of projects and the active participation of parents in school activities. Methods: This research used an exploratory descriptive method of quantitative approach. One used both an AUQEI assessment survey (Autoquestionnaire Qualité de Vie Enfant image) to evaluate the QL of students and the school’s sociodemographic records of students in order to analyze the familiar profile. One analyzed 82 students enrolled at the elementary school level. In order to compare the scores of the QL survey, one adopted the nonparametric Mann-Whitney test, with p ≤ 0.05 significance level. Results: The families of students were categorized in family-parents (married father and mother) and non-family parents (monoparentais) one responsible. Data releveled that 57.32% were family-parents, while 42.68% were non-family parents. Most families live from two to three kilometers far from the school and their income average is around three minimum wage. The main reason families choose for the school was the alternative pedagogical methodology adopted (90.9%), while 42.4% of choose the family education proposed by the school. However, the mean of the QL score of students with parental family was higher (escore 52,00) compared to non-family parents students (escore 50.48). However, the overall average of students’ QL score was higher (escore 52.4) in contrast with the cut-off score of 48. Conclusions: it is evident that the family factor is the great difference in the life of a child and a teenager. This fact is based on the high QL score of students with family-parents. However, the fact that the school is based on the pedagogy of projects must be highlighted as a means of bringing family-children-school together, mainly in terms of the rapprochement between children and parents who, in one way or another, have a disaggregated family life. This promotes well-being and transcendence.